Software-Defined Radio Testbed for 6G Research - Bengtsson, Vilgot; Wibeck, Melker; Wolf-Watz, Joel (My University, 2025)
As the demand on speed, coverage and bandwidth continues to increase for wireless communications, the sixth generation of mobile networks builds on and extends existing technologies. There is a testbed at Chalmers University of Technology focusing on the promising technology of distributed multiple input multiple output (D-MIMO). This project aims at assisting the D-MIMO testbed by constructing a flexible user equipment based on a software defined radio. Specifically, this is done by configuring the USRP B205mini-i, a universal software radio peripheral (USRP) from Ettus Research, in MATLAB to fully utilize its capabilities in signal processing and wireless communication. Trough simulations in MATLAB and physical testing of both wired and wireless transmissions, several key aspects are evaluated: the maximum bandwidth and its limitations on data rate, the relationship between signal duration and the on-board memory of the USRP, and the possibility of synchronizing multiple USRPs. Results show a maximum bandwidth of 41.24 MHz and a symbol rate of 10.31 Msym/s. Moreover, the result does not show a strict limitation on the signal duration as the USRP seems to stream data directly to and from the host computer. Synchronization is possible between two USRPs with a precision of a few microseconds at best. The USRP B205mini-i proves to be a flexible and cost-effective candidate for UE in the D-MIMO testbed. However, performance enhancements, such as lower-level configuration via FPGA programming, may be necessary depending on future system requirements.
Keywords: distributed MIMO; software-defined radio; USRP; 6G; wireless communication; signal processing; synchronization; testbed